2022
DOI: 10.1007/s40145-021-0549-z
|View full text |Cite
|
Sign up to set email alerts
|

Composition optimization, high-temperature stability, and thermal cycling performance of Sc-doped Gd2Zr2O7 thermal barrier coatings: Theoretical and experimental studies

Abstract: Sc was doped into Gd2Zr2O7 for expanding the potential for thermal barrier coating (TBC) applications. The solid solution mechanism of Sc in the Gd2Zr2O7 lattice, and the mechanical and thermophysical properties of the doped Gd2Zr2O7 were systematically studied by the first-principles method, based on which the Sc doping content was optimized. Additionally, Sc-doped Gd2Zr2O7 TBCs with the optimized composition were prepared by air plasma spraying using YSZ as a bottom ceramic coating (Gd-Sc/YSZ TBCs), and thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Compared with substitutional doping, interstitial doping in pyrochlore is better for achieving non-Vegard behavior of TEC in rare earth zirconates. Cations with much smaller size are doped into the lattice in the form of oxides, such as Mg 2+ and Sc 3+ [19][20][21]. First, the interstitial ions expand the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with substitutional doping, interstitial doping in pyrochlore is better for achieving non-Vegard behavior of TEC in rare earth zirconates. Cations with much smaller size are doped into the lattice in the form of oxides, such as Mg 2+ and Sc 3+ [19][20][21]. First, the interstitial ions expand the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal barrier coatings (TBCs) are popular for avoiding the direct exposure of metallic components to high temperatures. TBCs act as a thermal insulation layer that protects metallic component, thus enabling the component to operate at temperatures above the limit that would otherwise be imposed by the construction material [1][2][3][4][5][6]. As a result, TBCs saw their widespread applications and have become important to the development of new generation of gas turbines in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, rare earth (RE) zirconates (Gd 2 Zr 2 O 7 , La 2 Zr 2 O 7 , and Sm 2 Zr 2 O 7 ) reacted with CMAS melt to form apatite, which rapidly filled intergranular gaps and formed a dense barrier layer, preventing further penetration of CMAS. [18][19][20][21] Additionally, LnPO 4 (Ln = Nd, Sm, Gd) are also of excellent CMAS corrosion resistance. The related mechanism has been proposed that the formation of a denser, crack-free reaction layer mainly composed of Ca 3 Ln 7 (PO 4 )(SiO 4 ) 5 O 2 apatite, CaAl 2 Si 2 O 8 , and MgAl 2 O 4 is the key factor for high CMAS corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies revealed that some new TBC materials are of good CMAS resistance, which is derived from the fact that the rapid reaction of TBCs with CMAS generates a dense layer of reaction products, preventing further CMAS infiltration. For instance, rare earth (RE) zirconates (Gd 2 Zr 2 O 7 , La 2 Zr 2 O 7 , and Sm 2 Zr 2 O 7 ) reacted with CMAS melt to form apatite, which rapidly filled intergranular gaps and formed a dense barrier layer, preventing further penetration of CMAS 18–21 . Additionally, LnPO 4 (Ln = Nd, Sm, Gd) are also of excellent CMAS corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%